The Effectiveness of Personalized Learning Model in Developing Intensive English Reading Skills among Preparatory Stage Pupils - مروة محمد محمد موسي (Faculty of Education - Port Said University, 2020)
The present study aimed at investigating the effectiveness of the Personalized Learning Model in developing intensive English reading skills. The quasi- experimental design was used. The participants were a sample of (57) second year preparatory stage pupils at Fatima Al-Zahraa Governmental Language School at Port Said. The researcher selected two classes; the first class of (29) learners as an experimental group and the second one of (28) learners as a control group. An intensive English reading skills questionnaire was prepared by the researcher to identify the different levels of importance of some intensive English reading skills necessary for the second year preparatory stage pupils . An intensive English reading skills test was designed by the researcher to be used as an instrument to assess the pupils' progress in intensive English reading skills. The experiment was applied during the first term of the academic year2019/2020.The data obtained from the study has been analyzed statistically by SPSS program. Research results revealed significant differences between the post-test mean scores of the experimental and control groups in the intensive English reading skills in favor of the experimental group.